Keragaman Tumbuhan yang Dimanfaatkan Sebagai Pewarna Alami Batik Di Kabupaten Banyumas - Makdalena Viviliani Sir; Wiwik Herawati; Sukarsa Sukarsa (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Natural dyes are compounds that can be produced from various types of natural sources. Plants that produce natural dyes can be obtained from their parts such as leaves, bark, fruit skin, seeds, roots and flowers, which have gone through several processes, namely boiling, burning, crushing, pounding and immediately used. This study aims to determine the types of plants used as natural dyes for batik, and to determine which parts of plant organs are used as natural dyes for batik. The method used in this research is a survey method. Sampling was done by purposive sampling. Data were collected by observing and interviewing the batik home industry in Banyumas Regency. The parameters used are the types of plants and plant organs that are used as natural dyes for batik. Data were tabulated and identified for analysis. Analysis of the research data was carried out descriptively. Plant used as natural batik dyes in several Batik Home Industries in Banyumas Regency consists of 12 plant species the parts of plants were roots, stems, leaves, tubers, wood, bark, fruit skin, and coir. Natural dyes of batik are obtained by boiling and pounding. Then Used by Soaking, Dipping, and to draw motifs.